Greenland, view of Nathorst Tinde and Nordenskiöld Gletscher at Kejser Franz Joseph and Kjerulf Fjords - Boyd, Louise Arner, 1887-1972 (1931)
Nathorst Peak [Nathorst Tinde] (left), Nordenskiold Glacier [Nordenskiöld Gletscher], Franz Josef [Kejser Franz Joseph Fjord] and Kjerulf Fjords.